Plasmalogens of high-density lipoproteins (HDL) are associated with coronary artery disease and anti-apoptotic activity of HDL. Issue 2 (August 2015) - Sutter, Iryna; Velagapudi, Srividya; Othman, Alaa; Riwanto, Meliana; Manz, Jasmin; Rohrer, Lucia; Rentsch, Katharina; Hornemann, Thorsten; Landmesser, Ulf; von Eckardstein, Arnold
Abstract: Objective: Low high-density lipoprotein (HDL) cholesterol and loss of atheroprotective functions of HDL are associated with coronary artery disease (CAD). Here, we investigated the associations of HDL phospholipids with acute and stable CAD as well as with the anti-apoptotic activity of HDL. Methods: 49 species of phosphatidylcholines (PCs), lysophosphatidylcholines and sphingomyelins (SMs) as well as three species of sphingosine-1-phosphate (S1P) were quantified by liquid chromatography - mass spectrometry in HDL isolated from 22 healthy subjects as well as 23 and 22 patients with stable CAD and acute coronary syndrome (ACS), respectively. Native HDL and artificially reconstituted HDL (rHDL) were tested for their capacity to inhibit apoptosis of endothelial cells (ECs) induced by serum deprivation. Results: HDL of CAD or ACS patients differed from HDL of healthy controls by the content in nine of the 52 quantified phospholipid species as well as reduced anti-apoptotic activity. The capacity of HDL to inhibit EC apoptosis correlated significantly with five of eleven odd-chain PC's (= plasmalogens), two S1P's, SM42:2, PC34:2, and PC32:0. An orthogonal partial least square - discriminant analysis revealed independent associations of stable CAD with HDL-associated PC34:2, PC33:3 and PC35:2 as well as anti-apoptotic activity of HDL and of ACS with HDL-associated PC33:3, PC35:2, SM42:1, PC34:2 and PC36:2. rHDL reconstituted with apoA-I, PC34:1, and PC35:2 inhibited apoptosis of EC's more effectively than rHDL containing only apoA-I and PC34:1. Conclusions: The inverse association of HDL-plasmalogen levels with both stable and acute CAD may reflect direct anti-apoptotic effects of plasmologens on ECs. Highlights: Plasmalogens and sphingosine-1-phosphates (S1Ps) modulate the anti-apoptotic capacity of HDL towards endothelial cells. The inclusion of the plasmalogen PC35:2 improves the anti-apoptotic effect of reconstituted HDL towards endothelial cells. The content in plasmalogens PC33:3 and PC35:2 but not S1Ps is decreased in HDL of patients with ACS or CHD. Altogether the data suggest that some plasmalogens contribute to the antiatherogenic properties of HDL.